TEKNIK PENGUMPULAN DAN PENYALURAN ZAKAT, INFAK, DAN SEDEKAH PADA MITRA ZAKAT BAITUL MAAL HIDAYATULLAH KABUPATEN TULUNGAGUNG - Susilowati, Dwi; Santi, Mei (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
Abstract Hidayatullah Islamic Boarding School has a social institution called Baitul Maal Hidayatullah which focuses on da'wah and education. Apart from that, Baitul Maal Hidayatullah became Mitra Zakat, a part and partner of the National Amil Zakat Institution. Baitul Maal Hidayatullah is at the Surya Melati Hidayatullah Educational Institution Bandung Tulungagung. This research will look at how Baitul Maal Hidayatullah Zakat Partners, Tulungagung Regency collect and distribute zakat, infaq and alms. This research aims to find out how Baitul Maal Hidayatullah Zakat Partners, Tulungagung Regency collect donations, zakat funds and alms and how these funds are distributed. This research adopts a qualitative approach with descriptive methods as its basis. Information was collected through a documentation process and in-depth interviews; Data analysis is carried out through reduction, delivery and conclusions. Research findings show that there are three strategies for raising funds through zakat, infaq and alms: the traditional method involves visiting the prospective muzaki's home, where programs are presented in the form of proposals, and the muzaki can visit the office directly to make donations. Meanwhile, the modern approach utilizes online platforms that provide information related to the programs being implemented, with the use of social media to build sympathy from muzaki. In following the evolution of the times, this approach always adapts to technological advances that make transactions easier for muzaki. Donation funds were given directly to the Surya Melati Hidayatullah Bandung Tulungagung Educational Institution, to be further managed by the financial department in accordance with the zakat, infaq and alms program at Baitul Maal Hidayatullah Zakat Partners, Tulungagung Regency. Keywords: Technique, Collection, Distribution, Zakat, Infaq, Alms